Melting the ice: Project of students of American university in Bulgaria - Milošević Tijana (Temida, 2004)
Melting the ice is the project which aim is resolution of ethnic conflicts between Serbs and Albanians from Kosovo. The idea about the project came from several students of American University in Bulgaria (AUBG). The original idea of the project was to organize the series of panel discussions with participation of students, Serbs and Albanians. The main aim of the project is to help remove in confidence and prejudices and preparation of students to work on the same issue after coming back to their communities.